EVALUATION OF TRADITIONAL MEDICINES I: IDENTIFICATION OF PHELA USING DIFFERENT CHROMATOGRAPHIC TECHNIQUES - Lekhooa, Makhotso; Walubo, Andrew; Du Plessis, Jan JB; Matsabisa, Motlalepula C; Molefe, Duduzile (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
PHELA is a herbal mixture of four African traditional medicinal plants that has been used for decades in wasting conditions and is now being developed by the Medical Research Council (MRC) as an immune booster for patients with compromised immune system. A chromatographic fingerprint of PHELA was needed for quality control purposes. Here, a comprehensive method for fingerprinting of PHELA using different chromatographic techniques is described. It involved extraction of the PHELA by either acidic or a simple ‘salting-out’ method, followed by Thin Layer Chromatography (TLC) analysis and/or preparative Column Chromatography (CC). The products were thereafter analyzed by High Performance Liquid Chromatography with UV-detector (HPLC-UV), HPLC with fluorescence-detector (HPLC-FL) and Gas-Chromatography with a Mass Selective Detector spectrometer (GC¬MSD). The fingerprints were successfully used to differentiate PHELA from another common herbal product made from Hypericum perforatum (St. John’s Wort), thereby illustrating its high potential for use in fingerprinting of PHELA and in differentiating it from other herbal medicines. By validating the different chromatographic techniques on the standardized extraction methods, this approach will enable wide application in quality control of PHELA using acceptable procedures, thereby promoting effective monitoring of the finished product in all countries where it will be used.